The rotational spectrum of HD broadened by H2 at temperatures between 100 – 296 K. (January 2023) - Sung, Keeyoon; Wishnow, Edward H.; Drouin, Brian J.; Manceron, Laurent; Verseils, Marine; Benner, D. Chris; Nixon, Conor A.
Highlights: New measurements of HD and HD-H2 mixtures over the 50—360 cm −1 range, at temperatures 98-296 K, at pressures ≤ 1 bar. The R(0)—R(3) rotational transitions are observed in very high resolution spectra that were acquired using the AILES beam line at the Synchrotron SOLEIL, France. Spectroscopic line parameters are retrieved simultaneously for each transition using a multispectral fitting program. The measured collisional half widths, ∼0.01 cm −1 /atm at 296 K, are about five times smaller than the values listed in the molecular spectroscopy databases. Abstract: Laboratory measurements of the R(0) – R(3) pure rotational transitions of hydrogen deuteride (HD) have been performed at low pressures (< 1 bar) and temperatures between 98 and 296 K. The measurements were conducted using a Fourier transform spectrometer coupled to the Soleil synchrotron far-infrared source to obtain pure HD and HD-H2 mixture spectra. The observed spectra have been fitted using a non-linear least-squares multispectral fitting program. For each transition the line position, intensity, pressure broadening, pressure-induced frequency shift, and the temperature dependencies of these quantities have been determined simultaneously. These spectroscopic line parameters are compared to previous measurements made at higher gas pressures. Notably the present, and previous, measurements of the self- and H2 -broadened linewidths are smaller by a factor of five compared with those listed in the HITRAN and GEISA databases. This work is applicable to the low pressure, low temperature regimes found in the atmospheres of the giant gaseous planets. Graphical abstract: Figure HD and HD-H2 measured and fitted spectra. The lower part of each panel shows observed (dots) and calculated (solid) spectra. The upper portion shows the fitted residuals (obs-calc). All observed spectra, for each transition, are fit simultaneously such that the residuals are comparable to the measurement noise level. Image, graphical abstract